Viscometric Study on Polystyrene/polydimethylsiloxane Blends in Various Solvents - MELAD, OMAR; ABU-TEIM, OMAR; SOBEH, EHAB (Asian Journal of Chemistry, 2010)
The viscometric measurements were carried out for polystyrene (PS), polydimethyl siloxane (PDMS) and PS/PDMS in three different solvents at 25°C. The results showed that the choice of solvent is believed to play a key role in characterizing the viscosity behaviour of the polymer solution. The intrinsic viscosity and the viscometric interaction parameters have been experimentally measured for the binary (solvent/polymer) as well as for the ternary systems and also theoretically evaluated for the latter. The estimation of the compatibility degree in the different solvents have been done by means of the signs of Δb'm and Δ[η ]m . The results show that the compatibility of PS/PDMS blend in toluene while incompatibility in THF and benzene, respectively.